A startup vállalkozók személyiségjellemzőinek hatása az innovatív piaci jelenlétre - különös tekintettel az egészségügyi és orvosi biotechnológiai ágazatra - Lányi, Beatrix (Közép-Európai Közlemények, 2017)
The concept of entrepreneurship includes the establishment of a goal oriented organization with specific resource needs. Start-ups are innovative companies that are characterized by significant growth potential. New innovative start-ups overthrow the traditional ways of operation of long time ago established corporations, and they approach the concepts in new ways while making traditional attitudes outdated. Innovation, the process of bringing new products and services to market, is one of the most important issue today. Innovation is responsible for raising the quality and lowering the prices of products and services that have dramatically improved consumers’ lives. Medical biotechnology and healthcare industry can be mentioned among the most innovative sectors in Hungary. Start-ups are the drivers of this branch. Start-up entrepreneurs are considered innovative people who try to maximize profit and minimize costs while always carrying out something new. Personality and skills of a start-up entrepreneur have a significant effect on the innovativeness of the firm and as a consequence of this on its competitive advantage. Human factor stands in the focal point of my paper. In the article I investigated how the personality traits of entrepreneurs influence the market appearance and the presence of the innovative start-ups. Among the analytic methods of the personality we can distinguish nomothetic and idiographic ones. In this paper, I combined these two approaches for the deeper understanding of the issue. By using personality test and in-depth interviews, I highlighted how personality traits and creativity influence the innovative behavior of startup entrepreneurs in the medical biotechnology and healthcare industry.